Cultures of erudition and desire in university pedagogy - Psarologaki, Liana, 1983- author.
1 online resource (x, 63 pages).
Keywords: "This book promotes adult education in a university setting as cultivation and the inculcation of culture, democracy, and ethics beyond and through lived experience. It draws on theories from across disciplines, bringing together Aristotelian and post-structuralist thought. This includes Fernando Pessoa's notion of 'erudition' as culture and 'disquiet' as a mode of contemplative living, with Fernand Deligny's 'wanting' as manifestation of life. Liana Psarologaki addresses the pathologies of life and higher education in advanced capitalist societies and creates a manifesto for a new type of university pedagogy"--